Effects of Feeding Diet Rich in Mycotoxins on the Health and Growth Performances of Broiler Chicken - Okiki, P.A.; Ojiezeh, T.I.; Ogbimi, A.O. (International Journal of Poultry Science, 2010)
Low production performances in Nigerian poultry industry is of a serious concern. This study, an experimental exposure of broiler chicken to feed naturally contaminated with mycotoxins, is part of the efforts to unravel this problem of low productivity. Broiler chickens aged 1 day to 8 weeks were fed with diet compounded with naturally contaminated raw materials. Another set of day old broiler chicks were fed with feed compounded with high quality materials and served as control. Total aflatoxin and ochratoxin in each diet were determined by ELISA technique. The effects of mycotoxins on the birds were determined for growth performances, immunological status, as well as general well being of the birds. The total aflatoxin and ochratoxin concentrations in test feed were 200 ppb and 10 ppb respectively, while the control feed contained 15 ppb aflatoxin with no detectable level of ochratoxin. Birds fed with mycotoxin-rich diet had significantly lower growth performances (p = 0.012) and survival rate than control birds. Birds fed on mycotoxin rich diet had lower Infectious Bursal Disease (IBD) antibody titres (4280±1470) than controls (6780±1250), an indication of deleterious effect on body immune responses. There is need to monitor and enforce feed quality control in developing countries to ensure that poultry production is economically viable, so that the industry can grow.